2010
DOI: 10.3324/haematol.2009.016220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genomic risk factors on outcome after hematopoietic stem cell transplantation for patients with chronic myeloid leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundNon-HLA gene polymorphisms have been shown to influence outcome after allogeneic hematopoietic stem cell transplantation. Results were derived from heterogeneous, small populations and their value remains a matter of debate. Design and MethodsIn this study, we assessed the effect of single nucleotide polymorphisms in genes for interleukin 1 receptor antagonist (IL1RN), interleukin 4 (IL4), interleukin 6 (IL6), interleukin 10 (IL10), int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…22 Xiao showed that even in heterogeneous related and unrelated donor cohorts, certain TGFB and IL10 polymorphisms (TGFB1-509T/T genotype, IL10 -1092, -819CC and -592 C/C genotypes) were associated with GVHD and survival. 23 The absence of the IL10 genotype (ATA/ACC) in the donors, as shown in our sibling CML cohort, 11 was associated with decreased survival and death in remission. Absence of the ATA haplotype in the donors was also associated with Genomic risk factors in HCT for CML haematologica | 2012; 97 (7) 1017 © F e r r a t a S t o r t i F o u n d a t i o n death in remission in an unrelated and sibling Chinese transplantation population.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…22 Xiao showed that even in heterogeneous related and unrelated donor cohorts, certain TGFB and IL10 polymorphisms (TGFB1-509T/T genotype, IL10 -1092, -819CC and -592 C/C genotypes) were associated with GVHD and survival. 23 The absence of the IL10 genotype (ATA/ACC) in the donors, as shown in our sibling CML cohort, 11 was associated with decreased survival and death in remission. Absence of the ATA haplotype in the donors was also associated with Genomic risk factors in HCT for CML haematologica | 2012; 97 (7) 1017 © F e r r a t a S t o r t i F o u n d a t i o n death in remission in an unrelated and sibling Chinese transplantation population.…”
Section: Discussionmentioning
confidence: 56%
“…10 In general, these studies were based on small series and the results were not adjusted for the key risk factors for HCT outcomes. The role of non-HLA genetics was previously studied in a homogenous cohort of 228, primarily Caucasian, adult CML patients with HLA-matched sibling donors, transplanted from 1984-2003; 11 the results were reported to the EBMT. Among nine targeted cytokines, cytokine receptors, or other genes of interest, an intronic variable number tandem repeat within the gene for interleukin 1 receptor antagonist (ILIRA), a single nucleotide polymorphism (SNP) within the tumor necrosis factor II receptor superfamily, member 1B (TNFRSF1B) gene, and the interleukin 10 (IL10) gene were associated with survival when analyzed alone and alongside the EBMT risk score.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of a homogenous cohort of 228 HLA-identical sibling transplants for chronic myeloid leukemia, the absence of donor IL-10 ATA/ACC was associated with increased TRM and decreased OS. 21 Regarding IL-10 production, it is still debatable whether the GCC haplotype is associated with higher or lower IL-10 production in comparison to the ATA haplotype. In another study of unrelated donor transplants, TRM was associated with the higher IL-10 producer GCC haplotype when present in the donor.…”
Section: Discussionmentioning
confidence: 99%
“…To date, these studies with singlenucleotide polymorphisms (SNPs) have used small subsets of patients. [5][6][7][8][9] Although genome-wide association studies have been performed, 10 no SNP genotypes have been clearly identified so far that could be used to predict the outcome.…”
Section: Introductionmentioning
confidence: 99%